Biocatalytic asymmetric Michael addition reaction of l-arginine to fumarate for the green synthesis of N-(([(4S)-4-amino-4-carboxy-butyl]amino)iminomethyl)-l-aspartic acid lithium salt (l-argininosuccinic acid lithium salt). Issue 77 (16th October 2017) - Schoenenberger, B.; Wszolek, A.; Meier, R.; Brundiek, H.; Obkircher, M.; Wohlgemuth, R.
Abstract : The biocatalytic asymmetric Michael addition ofl -arginine to fumarate using argininosuccinate lyase (ASL) has enabled the synthesis of the key metabolitel -argininosuccinic acid lithium salt1 for the first time, with excellent yield and purity. Abstract : The basic natural amino acidl -argininosuccinate containing two chiral centers occurs inl -alanine, l -arginine, l -aspartate, l -glutamate andl -proline metabolic pathways and plays a role in the biosynthesis of secondary metabolites and other amino acids. It is a precursor for arginine in the urea cycle or the citrulline–NO cycle as well as a precursor to fumarate in the citric acid cycle via argininosuccinate lyase. We aimed to run part of the urea cycle in reverse by catalyzing not the elimination but the addition reaction ofl -arginine to fumarate in order to synthesizel -argininosuccinate. Argininosuccinate lyase (ASL) from Saccharomyces cerevisiae has been chosen as the catalyst for this addition reaction. The selected ARG4 gene was synthesized and homogeneously expressed in E. coli leading to a highly active argininosuccinate lyase. The ASL-catalyzed addition reaction ofl -arginine to fumarate has been successfully developed at gram scale. After a standard workup procedure the pure final productl -argininosuccinate has been isolated in good yield and high purity.